Brief Introduction on Manufacturing and Characterization of Metallic Electrode and Corresponding Modified Materials - Que Huang; Silong Wang; Yanjun Chen; Changcheng Liu; Qiyue Li (Metals, 2023)
As an important part in new energy storage devices, electrodes containing metals or their corresponding derivatives are widely used due to the diversity of material types, existing forms and assembly methods. In order to obtain novel energy storage components with superior performance, new technologies and studies on the improvement of electrode materials are emerging in recent years. This editorial paper aims to summarize the classical and latest research highlights on manufacturing, characterization and modification of metallic electrodes, especially new materials.